The Informational Role of Stock and Option Volume - Chan, Kalok; Chung, Y. Peter; Fong, Wai-Ming (Review of Financial Studies, 2002)
This article analyzes the intraday interdependence of order flows and price movements for actively traded NYSE stocks and their Chicago Board Options Exchange (CBOE)-traded options. Stock net trade volume (buyer-initiated volume minus seller-initiated volume) has strong predictive ability for stock and option quote revisions, but option net trade volume has no incremental predictive ability. This suggests that informed investors initiate trades in the stock market but not in the option market. On the other hand, both stock and option quote revisions have predictive ability for each other. Thus, while information in the stock market is contained in both quote revisions and trades, information in the option market is contained only in quote revisions.